Portable treatment system to treat cafeteria sullage water using effective microorganism and biomedia - Awang, Zarizi; Mohammad Isa, Muhammad Zahid (2020)
This study investigates portable water treatment in small scale size according to the design in the previous research that can solve the main problem of water pollution faced by UTHM Kampus Pagoh cafeteria. The objectives of this study are to design and produce a portable water treatment system using effective microbioorganism and biomedia to reduce contamination of sullage water and to analyze and make a comparative study with other designs to treat sullage water focusing on UTHM Kampus Pagoh cafeteria. To produce portable water treatment, a do-it-yourself (DIY) tank from polypropylene container box with volume of 151 L was designed, incorporating two types of biological treatments, namely effective microorganism and biomedia. This study also reviewed and compares the analysis results of biological oxygen demand (BOD), chemical oxygen demand (COD) and suspended solid of water treatment from previous studies. At the end of this study, the expected results obtained were comparable with results from the previous studies. As a recommendation, actual laboratory tests must be conducted for future work to obtain accurate data for the parameters analyzed .